Modern Christians in a Christianized Society - Fallding, Harold (Journal of Christian education, 2007)
There have been “Christianized” societies where Christian faith and standards are seen as the authentic guides for life. “Confrontation” is the Christian's principle of action. This entails ‘flying one's colours' in all situations, and probably encountering suffering by proclaiming broad moral principles with universal applicability. There is the need to cultivate a six-fold work:Feeding the flock and sending them out.Evangelizing.Pronouncing publicly on true moral standards.Supporting and challenging the governing authority.Pioneering social reform and relief, andProviding for sociability.In addition, there is the need for church reorganization over time.